New Economic Sociology: What Has Been Accomplished, What Is Ahead? - Ричард Сведберг (Journal of Economic Sociology, 2010)
Hereby the main part of the well-known paper about new economic sociology by Richard Swedberg is presented. The paper deals with the origin of the new economic sociology connected firstly with the published articles by Granovetter in 1980s. The author characterizes its three key directions for the development. We provide the second translation of this paper  (the first translation was published by the “Journal of sociology and social anthropology” [2002. Т. 5. № 2. С. 13 – 35]), which comprises a range of considerable important adjustments to this basic text.